3D printed structured porous hydrogel promotes osteogenic differentiation of BMSCs. (March 2023) - Hao, Xiaotian; Miao, Sheng; Li, Zhiquan; Wang, Taoran; Xue, Baobao; Chen, Jingdi; Xian, Chunxing; Bi, Long
Graphical abstract: Highlights: The structured porous hydrogel scaffolds were fabricated by 3D printing. The porous structure is more conducive to the activity and proliferation of cells in the hydrogel. The porous structure promotes the expression of osteogenesis-related genes of BMSCs in hydrogel scaffolds. Structured porous hydrogels produce more mineralization in vivo . Abstract: Hydrogel is a suitable material for three-dimensional cell culture, and is rich in water content and can better simulate a natural extracellular matrix. However, the relatively compact pores in the interior often inhibit the growth and differentiation of containing cells. Additionally, the impact of the pore structure on the differentiation of cells remains to be unknown. In this work, porous hydrogel scaffolds with medium pore sizes (100–1000 μm) were prepared using 3D printing technology, and the hydrogel scaffolds without pores and non-printed hydrogel scaffolds were designed as control to investigate the effect of 3D printed porous structures on osteogenic differentiation of BMSCs within hydrogel scaffolds, both in vitro and in vivo . The pore structure of 3D printed structured porous scaffold was explicitly inspected by SEM. The water content and expansion rate of hydrogel did not change, despite its porous structure. The BMSCs were evenly distributed across the porous scaffold and maintained high activity, thus benefiting from the sufficient circulation and diffusion of oxygen and nutrients due to the regular pores. In vitro, the osteogenic differentiation of BMSCs in the structured porous hydrogels was more prominent compared to the non-porous groups. Moreover, the mineralization of the hydrogel scaffolds was also enhanced. After ectopic implantation in the posterior gluteal muscle punch, the structured porous hydrogel exhibited relatively good mineralization and ectopic osteogenesis by the three-dimensional reconstruction of micro-CT, collagen staining, and immunological analysis. The 3D printing-based approach provides a facile strategy for the preparation of hydrogels with intermediate pore structures. This can promote the viability and osteogenic differentiation of BMSCs in hydrogel scaffolds.